2022
DOI: 10.3389/fped.2022.864029
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Science in Pediatric Critical Care – Sedation and Analgesia Practices as a Case Study

Abstract: Sedation and analgesia (SA) management is essential practice in the pediatric intensive care unit (PICU). Over the past decade, there has been significant interest in optimal SA management strategy, due to reports of the adverse effects of SA medications and their relationship to ICU delirium. We reviewed 13 studies examining SA practices in the PICU over the past decade for the purposes of reporting the study design, outcomes of interest, SA protocols used, strategies for implementation, and the patient-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…ICU-based rehabilitation has been recommended as a standard of care for all critically ill patients (4, 6); however, its adoption into routine practice remains suboptimal in adult ICU and PICU globally, with delirium monitoring, choice of sedation, and early mobilization being the most challenging to implement (12, 36). Evidence-based implementation strategies are therefore crucial for translating evidence into practice (14, 37). This study demonstrates that a bundle consisting of an analgesia-first sedation approach, delirium monitoring and prevention, and early mobilization, can be successfully implemented in two PICUs over 26 months using a clear implementation strategy and process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ICU-based rehabilitation has been recommended as a standard of care for all critically ill patients (4, 6); however, its adoption into routine practice remains suboptimal in adult ICU and PICU globally, with delirium monitoring, choice of sedation, and early mobilization being the most challenging to implement (12, 36). Evidence-based implementation strategies are therefore crucial for translating evidence into practice (14, 37). This study demonstrates that a bundle consisting of an analgesia-first sedation approach, delirium monitoring and prevention, and early mobilization, can be successfully implemented in two PICUs over 26 months using a clear implementation strategy and process.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, this study highlights the importance of using an evidence-based framework for implementing quality improvement, and tailoring the process to the resources and needs of the local setting. Successful implementation does not need to be driven by researchers; it requires leadership, team collaboration, strategic planning, and implementation science methodology (14). We demonstrated that it is possible to introduce a PICU-rehabilitation bundle using large (site 1) and small (site 2) teams, respectively; essential to the process is that the teams consist of stakeholders, there are clear roles and responsibilities, objectives and timelines, and that support and guidance are available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesizing the existing barriers and facilitators to using procedural pain treatments in pediatric patients is the premise of developing effective strategies. (37)(38)(39). Therefore, this systematic review will synthesize barriers and facilitators in the literature under the guidance of implementation science and evaluate the importance of different factors (37).…”
Section: Introductionmentioning
confidence: 99%